Bagaimana Struktur Kepemilikan, Board size dan Leverage Berpengaruh Terhadap Profitabilitas - Hajrah Hamzah; Masnawaty Sangkala (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2022)
This study aims to examine whether leverage, ownership structure and board size affect the profitability of a company's financial statements that are included in the LQ-45 partially or simultaneously. In this study using the documentation method in order to collect data where this data is in the form of a company's annual financial report document obtained from the official length of the Indonesian Stock Exchange and then tested using multiple linear regression analysis techniques. The results of the t test show that partially institutional ownership has a positive effect on profitability where the significance is 0.014<0.05, managerial ownership has a negative effect on profitability where the significance is 0.142>0.05, then for board size has a positive effect on profitability, the significance value 0.041<0.05, and leverage has a negative effect on profitability where the significance value is 0.682>0.05. Then for the simultaneous effect of all independent variables have an influence on profitability